Transcutaneous electrical acupoint stimulation for pregnancy outcomes in women undergoing in vitro fertilization-embryo transfer: A systematic review and meta-analysis - Yang, Han; Hu, Wen-hui; Xu, Gui-xing; Yin, Zi-han; Yu, Si-yi; Liu, Jia-jia; Xiao, Zhi-yong; Zheng, Xiao-yan; Yang, Jie; Liang, Fan-rong (Frontiers in Public Health, 2022)
Objectives: To conduct a systematic review and meta-analysis to assess whether transcutaneous electrical acupoint stimulation (TEAS) is effective and safe to improve the pregnancy outcomes for women undergoing in vitro fertilization-embryo transfer (IVF-ET) . Methods: Eight online databases were searched from inception to November 19, 2021. In addition, four clinical trial registries were also searched, relevant references were screened, and experts were consulted for possible eligible studies. Randomized controlled trials (RCTs) which included patients with infertility who underwent IVF and used TEAS as the main adjuvant treatment versus non-TEAS or mock TEAS control were included. The clinical pregnancy rate (CPR) was considered as the primary outcome. Live birth rate (LBR), biochemical pregnancy rate (BPR), ongoing pregnancy rate (OPR), early miscarriage rate (EMR), and adverse events related to interventions were regarded as secondary outcomes. The selection, data extraction, risk of bias assessment, and data synthesis were conducted by two independent researchers using Endnote software V.9.1 and Stata 16.0 software. Results: There were 19 RCTs involving 5330 participants included. The results of meta-analyses showed that TEAS can improve CPR (RR = 1.42, 95% CI (1.31, 1.54)), HQER (RR = 1.09, 95% CI (1.05, 1.14)), LBR (RR = 1.42, 95% CI (1.19, 1.69)), and BPR (RR = 1.45, 95% CI (1.22, 1.71)) of women underwent IVF-ET with low, low, moderate, and low quality of evidence, respectively. There was no significant difference in EMR (RR = 1.08, 95% CI (0.80, 1.45)) and BDR (RR = 0.93, 95% CI (0.13, 6.54)) with very low, and moderate quality of evidence, respectively. Cumulative meta-analysis showed that the effect value of TEAS versus controls was relatively stable in 2018 (RR = 1.52, 95% CI (1.35, 1.71)). In addition, no serious adverse events associated with TEAS were reported. Conclusion: Our findings suggest that TEAS may be effective and safe for women undergoing IVF-ET to improve pregnancy outcomes. However, the current evidence quality is limited, and more high-quality RCTs are needed for further verification in the future.